O processo de construção tecno-artística por meio da reciclagem - Palhaci, Maria do Carmo Jampaulo Plácido [UNESP]; Nicola, Ricardo Luis [UNESP]; Hellmeister, Luiz Antonio Vasques [UNESP] (My University, 2013)
The recycling in Engineering can be used for reuse of material disposed remains into the environment. The recycling of construction residues comes from antique and was applied in the reconstruction of Europe after World War II. From the environmental point of view, the main problem with the residues that can be recycled, is related to its irregular deposition and the large volumes produced. In this article we aim to approach the recycling techniques through literature surveys and propose techno-artistic works that solve the problem of wasting residues in our planet.
Keywords: Art; Recycling; Residues construction; Sustainability